Systemic treatments and outcomes in CIC‐rearranged Sarcoma: A national multi‐centre clinicopathological series and literature review. (17th February 2022) - Connolly, Elizabeth A.; Bhadri, Vivek A.; Wake, Johnathon; Ingley, Katrina M.; Lewin, Jeremy; Bae, Susie; Wong, Daniel D.; Long, Anne P.; Pryor, David; Thompson, Stephen R.; Strach, Madeleine C.; Grimison, Peter S.; et al.
Abstract: CIC ‐rearranged sarcoma is a recently established, ultra‐rare, molecularly defined sarcoma subtype. We aimed to further characterise clinical features of CIC ‐rearranged sarcomas and explore clinical management including systemic treatments and outcomes. Methods: A multi‐centre retrospective cohort study of patients diagnosed between 2014–2019. Results: Eighteen patients were identified. The median age was 27 years (range 13–56), 10 patients were male (56%), 11 patients (61%) had localised disease and 7 patients had advanced (metastatic or unresectable) disease at diagnosis. Of 11 patients with localised disease at diagnosis, median overall survival (OS) was 40.6 months and the 1‐, 2‐ and 5‐year OS estimates were 82%, 64% and 34% respectively. Nine patients (82%) underwent surgery (all had R0 resections), 8 (73%) patients received radiotherapy to the primary site (median dose 57Gy in 28 fractions), and 8 (73%) patients received chemotherapy (predominantly Ewing‐based regimens). Metastases developed in 55% with a median time to recurrence of 10.5 months. In patients with advanced disease at diagnosis, median OS was 12.6 months (95% CI 5.1–20.1), 1‐year OS was 57%. Median progression‐free survival was 5.8 months (95% CI 4.5–7.2). Durable systemic therapy responses occurred infrequently with a median duration of systemic treatment response of 2.1 months. One durable complete response of metastatic disease to VDC/IE chemotherapy was seen. Responses to pazopanib ( n = 1) and pembrolizumab ( n = 1) were not seen. Conclusion: In this series, CIC ‐rearranged sarcomas affected young adults and had a high incidence of presenting with, or developing, metastatic disease. The prognosis overall was poor. In advanced disease, durable systemic therapy responses were infrequent. Abstract : Multi‐centre retrospective series of systemic therapy and outcomes for recently established ultra‐rare sarcoma subtype. CIC‐rearranged sarcomas appear to be relatively chemo‐insensitive as illustrated by a high frequency of relapse in localised disease and short durations of treatment response in the advanced setting. In advanced disease, durable systemic therapy responses in CIC‐rearranged sarcoma are limited with a median duration of systemic treatment response of 2.1 months in this series.